2021
DOI: 10.2196/26202
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Methods of Meeting Sexual Partners and Sexual Practices Among Heterosexuals: Cross-sectional Study in Melbourne, Australia

Abstract: Background The association between meeting partners on the web and sexual practices has been understudied in heterosexuals. Objective This study aims to examine the associations between the methods of meeting partners and sexual practices and HIV and sexually transmitted infections (STIs) in heterosexuals. Methods We conducted a survey among heterosexuals attending the Melbourne Sexual Health Centre in 2019.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Such responses suggest students may be concerned to overstep any boundaries related to the application of mate choice social behaviours outside of traditional contexts like social venues or meeting via family and friends (Constantinou et al ., 2021). In these traditional and socially accepted situations, it is often an explicit expectation that both parties are actively searching for a mate, thereby mutually clarifying social behaviours and establishing goal congruence for value creation.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Such responses suggest students may be concerned to overstep any boundaries related to the application of mate choice social behaviours outside of traditional contexts like social venues or meeting via family and friends (Constantinou et al ., 2021). In these traditional and socially accepted situations, it is often an explicit expectation that both parties are actively searching for a mate, thereby mutually clarifying social behaviours and establishing goal congruence for value creation.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…We conducted a cross-sectional survey named 'Annual Sexual Practices and Activities (ASAP)' at the Melbourne Sexual Health Centre (MSHC) between March and April 2019. 22,24,25 The MSHC is the largest public sexual health clinic in Victoria, Australia, and it provided approximately 50 000 consultations in 2019. Clients attending the MSHC are asked to complete a series of questions on demographic characteristics and sexual practices via computer-assisted self-interviewing (CASI) as part of routine care and management.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have examined same-sex kissing partners among MSM 13,[18][19][20] or opposite-sex kissing partners among heterosexuals. 21,22 Some MSM would also have sex with women and it is unclear how commonly MSM would kiss women with and without sex. Given oropharyngeal gonorrhoea is mostly asymptomatic 9 and MSM have a high prevalence of oropharyngeal gonorrhoea, 8,23 it is possible that gonorrhoea can be transmitted between MSM and women via kissing in the absence of sex.…”
Section: Introductionmentioning
confidence: 99%
“…Garga and co-workers found that individuals with more than one sexual partner, those who have high-risk behaviour, and those who have casual sex without discussion about sexually transmitted infections were more likely to use these dating apps [6]. Another study found that men who found their partners online were more likely to pay for sex compared with those who met partners at social venues [7]. A meta-analysis found that sexual encounters that were initiated online were more likely to have unprotected anal intercourse, whereas recent studies have found that app-users were more likely to have sexually transmitted infections (gonorrhea, chlamydia, and syphilis) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%